Pengaruh Populasi Kacang Tanah (Arachis hypogaea L.) dan Jagung (Zea mays L.) terhadap Pertumbuhan dan Produksi Pada Sistem Pola Tumpang Sari - Adria Sartika br Sembiring; Jonis Ginting; Ferry Ezra Sitepu (Universitas Sumatera Utara, 2015)
The purpose of the study was to determine the effect of the number of peanut and corn population tothe growth and yield in intercropping pattern system. The research was conducted at LambarVillage Tigapanah District Karo Regency, North Sumatera with the height of ±1200metres abovesea level, began from November 2013 until May 2014. The research was arranged with arandomized block design with two factors. The first factor was peanut population (20x20 cm, 30x20cm, 40x20 cm, 50x20 cm) and the second was corn population (60x20 cm, 70x20 cm, 80x20 cm).The parameters observed were peanut height, number of peanut leaf, corn height, number of cornleaf, number of pod per sample, peanut production per plot, weight of 100 peanut grain, peanut leafarea index, wet weight of corn cob, dry weight of corn cob, and corn production per plot. Theresults showed that corn height, number of corn leaf, peanut production per plot, weight of 100peanut grain, wet weight of corn cob, and peanut leaf area index were significantly affected bypopulation of peanut. Population of corn significantly affected the wet weight of corn cob, dryweight of corn cob, and corn production per plot. Analysis of data showed that the interaction ofpeanut and corn population were founded and significantly affected the corn height, number of cornleaf, and weight of 100 peanut grain.Keywords : peanut, corn, population.